Antiferromagnetismo e ordem oculta em um modelo de Anderson - Lausmann, Ana Claudia (2018)
In the absence of an external magnetic field, the heavy-fermion compound URu2Si2 exhibits a second-order phase transition at 17.5 K. This transition is marked by a mean-field-like anomaly in the specific heat, by the existence of anisotropic magnetic susceptibility, and by a huge loss of entropy. Measurements on URu2Si2 show that this transition produces a gap with magnitude between 7.5 and 5 meV which develops over 40% of the Fermi-surface. Despite intensive theoretical and experimental research, even after almost thirty years, the nature of the hidden order phase, as it is called, remains unraveled. Initially, it was thought that this transition was a kind of antiferromagnetic transition. However, pressure measurements showed that a transition to an antiferromagnetic state occurs only above 0,5 GPa. Recently, a theory based in the underscreened Anderson Lattice Model has been proposed to describe the order parameter of the hidden order phase (RISEBOROUGH; COQBLIN; MAGALHAES, 2012) of URu2Si2. In the present work, we show that the proposed model exhibits a delicate competition between the “Hidden Order” and a Neel antiferromagnetic phase, and that it might also describe the first-order transition in URu2Si2 found by applying pressure. We assume that the pressure has the effect of increasing both the tight-binding hopping integrals for the conduction and the 5f bands. We observe that the “Hidden Ordered” state only appears for a very limited range of occupation numbers. The analysis of the Helmholtz Free Energy shows a Neel antiferromagnetic state followed by a “Hidden Order ” state and then a second Neel antiferromagnetic state as the band widths are increased. The bondaries of the paramagnetic state are obtained via second-order instabilities. The Neel antiferromagnetic state also was investigated.The results show a region of first order transitions between two antiferromagnetic phases, ending at a critical point. Besides that, there is a tricritical point at the low temperature and high value of band width region. Also, it was verified changes on Fermi surface topology in the Neel antiferromagnetic state and a parcial reconstruction on Fermi surface. This reconstruction follows the line of first order transition between the antiferromagnetic phases and it extends beyond the critical point, suggesting that there may be a Lifshitz transition in this region of parameters.